Calculation of propulsive forces in ski skating - Göpfert, C. (3rd International Congress on Science and Nordic Skiing - ICSNS 2015. 5-8 June 2015, Vuokatti, Finland, 2015)
To generate propulsion efficiently is an essential goal in cross-country skiing and largely determines the athlete's performance (Smith, 2008). Great effort has been made in cross-country (XC) skiing research to develop force measurement systems and to determine the propulsive force component acting in the direction of skiing (Smith, 2008). However, which share of applied ground reaction forces (GRF) ultimately lead to acceleration of the center of mass (COM) in skiing direction, thus to propulsion of the athlete, is unclear. The propulsion of the XC-skier could fundamentally be measured by video or motion capture systems investigating the movement of the COM. However, to gather information on the contribution of each thrust phase, components of propulsion have to be determined independently. Thus, this work is aimed at (1) calculating the propulsion of the skier, represented by his COM, from 3D force and motion capture data, (2) applying the calculation on an example in V2A skating, (3) comparing the calculation of propulsion and propulsive forces and (4) testing, if propulsion can be calculated also from pressure insole data or 1D/2D force binding data.